Available online Design and simulation of multistream plate-fin heat exchangers – Single-phase streams. (5th January 2016) - Montanez-Morantes, Maria; Jobson, Megan; Zhang, Nan
Highlights: Models to predict performance are suitable for operational optimisation. Model uses geometry data to predict heat transfer coefficient and pressure drop. Regressed model estimates heat exchange per stream based on operational data. Design methodology achieves integer numbers of passes of equal length per stream. Simulation methodology shows good accuracy (outlet temperatures within 3 °C). Abstract: Widely known cryogenic processes, such as LNG, ethylene or air separation plants, make use of plate-fin heat exchangers (PFHEs) because of their compactness and ability to exchange heat simultaneously between the different streams that flow through it. However, this ability to simultaneously exchange heat makes their design and simulation a complex task. An accurate model that is able to predict their performance (i.e. simulate PFHEs) for different operating conditions is needed to be able to optimise the operation of plants that make use of PFHEs. However, little research has addressed this subject. In the present work, several methodologies are proposed for the design and simulation of PFHEs for single-phase streams. In this work, a design methodology is proposed that addresses the shortcomings of previous methodologies. For the simulation of PFHEs, a superstructure approach is used and the PFHE is represented as a network of two-stream heat exchangers. Two different methodologies are proposed for the simulation of PFHEs: one model makes use of detailed geometry data to make thermal-hydraulic calculations (i.e. heat transfer coefficient and pressure drop calculations); the other model regresses a number of parameters based on available operational data and then makes use of these parameters to estimate the heat exchange between streams. The benefits of using the design and simulation methodologies proposed are illustrated with an example taken from the open literature. The results show that all of the models are able to predict with good accuracy the outlet temperatures and thermal-hydraulic behaviour of these exchangers.